High temperature deformation mechanism and microstructural evolution of relatively lightweight AlCoCrFeNi high entropy alloy. (April 2020) - Tian, Quanwei; Zhang, Guojin; Yin, Kexin; Wang, Ling; Wang, Wenwen; Cheng, Weili; Wang, Yinong; Huang, J.C.
Abstract: The high temperature compressive characteristics of relatively light weight AlCoCrFeNi HEA were investigated via compression tests in a wide deformation temperature ( T ) range of 1073–1373 K and strain rate ( ε ˙ ) range of 10 −3 –1 s −1 . Hot deformation led to the phase constitution transformation from the disorder BCC (A2) + order BCC (B2) at the room temperature to FCC + A2+ B2 +σ at 1073 K and 1173 K, and then to FCC + A2+B2 phase at 1273 K and 1373 K. The kinetic analysis was performed based on the flow stress data by using the hyperbolic sine law constitutive models with a higher the correlation coefficient ( R 2 ). Using combination of kinetics analysis and microstructure evolution results, it can be concluded that there was a gradual transformation of the dominant deformation mechanism from the symbiosis effects of grain boundary sliding (GBS) in fine grains and local dislocation gliding in coarse grains at 1073 K to the dislocation climbing mechanisms at 1373 K. The flow stress decreased with the decreasing strain rate and/or increasing true strain, as well as the deformation temperature. At 1073 K and 1173 K, the flow softening was primarily associated with the GBS of ultrafine dynamic recrystallization (DRX) grains in the local phase transformation regions, as well as the dynamic precipitation of FCC phases. While, the softening effect was primarily controlled by the dynamic precipitation of FCC phases and dynamic recovery (DRV) at 1273 K. When the deformation temperature rose to 1373 K, the main softening mechanisms were the continuous DRX (CDRX) and DRV, as well as the coarsening and dissolution of A2 phases . Moreover, the clear serration behaviors at 1373 K/1s −1 and 1373 K/10 −3 s −1 were induced by the interaction effect between the dislocation and cluster. Highlights: Hot deformation behaviors of AlCoCrFeNiHEA under a wide working condition were firstly reported. Hot deformation mechanisms were determined on the kinetics analysis and microstructure. Flow softening effects associated with microstructural features were analyzed.